2007
DOI: 10.1016/j.jmr.2007.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Measuring nanopore size from the spin–lattice relaxation of CF4 gas

Abstract: The NMR 19 F spin-lattice relaxation time constant T 1 for CF 4 gas is dominated by spin-rotation interaction, which is mediated by the molecular collision frequency. When confined to pores of approximately the same size or smaller than the bulk gas mean free path, additional collisions of molecules with the pore walls should substantially change T 1 . To develop a method for measuring the surface/volume ratio S/V by measuring how T 1 changes with confinement, we prepared samples of known S/V from fumed silica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…The T 1 relaxation times are sensitive to the magnetic field, temperature, and the PFC microenvironment. In this case, the nanoparticles themselves could be affecting the relaxation of PFCs, likely due to both a decrease in molecular mobility of PFC inside of UMNs and the molecular interactions between the SiO 2 cage and PFC. , Degradation of the silica nanoparticles may change the response curve of PFC to oxygen. As an initial evaluation of the PERFUMN stability, a preliminary analysis in whole blood is described in the section PERFUMN Oxygen Measurements in Whole Blood.…”
Section: Resultsmentioning
confidence: 99%
“…The T 1 relaxation times are sensitive to the magnetic field, temperature, and the PFC microenvironment. In this case, the nanoparticles themselves could be affecting the relaxation of PFCs, likely due to both a decrease in molecular mobility of PFC inside of UMNs and the molecular interactions between the SiO 2 cage and PFC. , Degradation of the silica nanoparticles may change the response curve of PFC to oxygen. As an initial evaluation of the PERFUMN stability, a preliminary analysis in whole blood is described in the section PERFUMN Oxygen Measurements in Whole Blood.…”
Section: Resultsmentioning
confidence: 99%
“…Other NMR approaches, developed recently, are based on relaxation behavior of gases when they saturate pores of materials. For example, the 19 F T 1 times of CF 4 gas, typically measured as 0.2 to 5−6 ms and dominated by spin-rotation interaction, have been applied for pore-size measuring . The relaxation measurements have shown that the gas, condensed on the pore walls and in a region near the wall, is denser than the bulk gas.…”
Section: Solid-state Nmr In Materials Chemistry: Diamagnetic Molecula...mentioning
confidence: 99%
“…This can be explained by increased collisions among adsorbed gas molecules with a higher density and also collisions with the pore surface. 48 The gas−gas collision rate can be estimated by…”
mentioning
confidence: 99%
“…For the relaxation induced by the gas molecules, simulation results show that the spin–rotational interaction still dominates, as in the bulk phase, but is smaller than that of the bulk phase over an order of magnitude (Figures S5–S7 in Supporting Information). This can be explained by increased collisions among adsorbed gas molecules with a higher density and also collisions with the pore surface . The gas–gas collision rate can be estimated by ω g = 2 π d M 2 w / V normalc normala normalg normale where v̅ is the mean velocity, d M is the kinetic diameter of the CH 4 molecule, w is the number of molecules per cage, and V cage is the volume of a ZIF-8 cage.…”
mentioning
confidence: 99%
See 1 more Smart Citation